Pre-Service Teachers’ Beliefs, Difficulties and Practices Toward Inquiry-Based Learning in Mathematics: A Mixed-Method Approach - Benitez, John Laurence H.; Quijada, Rachel An; Ragas, Amelyn Mae L.; Gono Jr., Exequiel R. (European Scientific Journal, ESJ, 2026)
This study explored pre-service teachers’ (PSTs) beliefs, perceived difficulties, and classroom practices toward inquiry-based learning (IBL) in mathematics at a private university in Davao City, Philippines. Employing a convergent mixed-methods design, quantitative data were collected from 92 PSTs via a validated survey (Cronbach’s α = 0.872–0.885), assessing beliefs, difficulties, and practices on a 5-point Likert scale. Qualitative data came from semi-structured interviews and focus groups with 15 purposively selected PSTs. Results showed strong beliefs (M = 4.27, SD = 0.48) in IBL’s effectiveness for critical thinking and engagement, but high perceived difficulties (M = 4.35, SD = 0.44) from time constraints, resource limitations, and student readiness. Practices scored moderately (M = 3.83, SD = 0.54), revealing a theory-practice gap confirmed qualitatively through themes like "Deep, Active Learning," "Constraints and Barriers," and "Teacher as Facilitator." Quantitative-statistical trends aligned with qualitative narratives, triangulating that PSTs value IBL theoretically but struggle with practical execution under curriculum pressures. Conclusions highlight the need for teacher education programs to bridge this gap through targeted professional development, IBL-compatible lesson design, scaffolded inquiry training, and institutionalized mentorship. Recommendations emphasize embedding inquiry cycles (orienting, planning, investigating, concluding) into curricula and using real-world problems to foster curiosity. This study contributes Philippine-context evidence supporting SDG 4 (quality education), informing pre-service training for student-centered mathematics pedagogy.